2019
DOI: 10.21203/rs.2.17596/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRA2A-induced upregulation of LINC00662 regulates blood-brain barrier permeability by affecting ELK4 mRNA stability in Alzheimer's microenvironment

Abstract: The blood-brain barrier (BBB) plays a pivotal role in maintenance and regulation of the neural microenvironment. The occurrence of BBB disruption is the pathological change of early Alzheimer’s disease (AD). RNA-binding proteins and long non-coding RNAs are involved in the regulation of BBB permeability. Our study was performed to demonstrate TRA2A/LINC00662/ELK4 axis in regulating BBB permeability in AD microenvironment. In Aβ1-42-incubated microvascular endothelial cells (ECs) of BBB model in vitro, TRA2A an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Indeed, another lncRNA, LINC00662, was recently reported to bind with TRA2A. This interaction increases LINC00662 stability, thereby to regulate blood-brain barrier permeability in the Alzheimer's microenvironment [28]. In addition, we have demonstrated that the binding of TRA2A to MALAT1 controls the EZH2/β-catenin pathway in siRNA depletion assay.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, another lncRNA, LINC00662, was recently reported to bind with TRA2A. This interaction increases LINC00662 stability, thereby to regulate blood-brain barrier permeability in the Alzheimer's microenvironment [28]. In addition, we have demonstrated that the binding of TRA2A to MALAT1 controls the EZH2/β-catenin pathway in siRNA depletion assay.…”
Section: Discussionmentioning
confidence: 57%